Kualitas keju segar dengan penambahan Tepung Porang (Amorphophallus onophyllus) dan kultur tunggal Lactobacillus rhamnosus - Ismiarti Ismiarti; Aria Dipa Tanjung; Rima Dwi Sari (Jurnal Ilmu Peternakan Terapan, 2023)
Cheese is one milk-based livestock product that has a chance to be a functional food by combining probiotics and prebiotics. The study aimed to develop synbiotics cheese from cow milk with the addition of porang flour as prebiotic and Lactobacillus rhamnosus as a probiotic that will give health benefits to the host. The experimental study used a Completely Randomized Design (CRD) factorial pattern 4x3 with 3 replications. The first factors consisted of P0 (soft cheese without porang flour and Lacobacillus rhamnosus), P1 (soft cheese with 0.03% porang flour), P2 (soft cheese with 5% Lactobacillus rhamnosus), and P3 (soft cheese with 0.03% porang flour + 5% Lactobacillus rhamnosus). The second factors were storage T0 (0 days), T1 (7 days), and T2 (14 days) at a temperature rate of 4-10°C. Variables measured were pH value, total titratable acidity (TTA), free fatty acid (FFA), and a total of Lactic Acid Bacteria (LAB). Data were analyzed using analysis of variance (ANOVA) with post hoc test Duncan’s Multiple Range Test (DMRT). It resulted that the addition of porang flour and Lactobacillus rhamnosus significantly affected (P<0.05) pH, TTA, FFA, and a total of LAB, in line with storage that also significantly affected all parameters measured (P<0.05). Interaction between the addition of porang flour and Lactobacillus rhamnosus was significantly affected (P<0.05) to pH, TTA, LAB, and a total of LAB. In summary, the addition of porang flour and Lactobacillus rhamnosus produced soft cheese that had the potency to be a functional food.